Applications of Membrane Hydrocyclone Recovery of Silicon Carbide Powder - Tsai, Yen-Cheng; Hsu, Chen-Yang; Wu, Rome-Ming (Proceedings of Engineering and Technology Innovation, 2020)
This work investigated the possibility of using membrane hydrocyclone as a separator to recover the silicon carbide powder. The weight percentage of silicon carbide powder is 62.9%. Classifying these powders by a 2.5 cm-diameter hydrocyclone that equips membrane tube in the center position, overflow and underflow are obtained. The results of the primary separation show that the overflow and underflow are about half of the proportion of solid, but silicon carbide powder content in the overflow is higher. Therefore, it is necessary to consider the recovery of silicon carbide powder contained in the overflow.